Implementasi Hukum Pidana Bagi Pengedar Obat dan Makanan Illegal Pada Tingkat Penyidikan di Wilayah Hukum Kalimantan Barat (Studi Kasus Balai Besar POM (BBPOM) di Pontianak) - Pratama, Yogi; Hermansyah, Hermansyah (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This study is a follow-up study with an expansion of the scope of previous research around the provisions and implementation of binding law enforcement regarding the circulation of illegal Medicines and Food at the investigation level, finding and ensuring authorized institutions in handling the circulation of illegal Medicines and Food in the West Kalimantan jurisdiction review, as well as explaining concrete events, reconditioning, and solutions of the emergence of illegal Medicines and Food circulation in West Kalimantan. This study uses the method of normative-empirical research (applied law research) on the implementation of normative legal provisions (laws) in action on any particular legal events that occur in a society or view the law as a reality, including social reality, the fact of culture and this study is descriptive with the findings of the BBPOM in Pontianak as a Technical Service Unit (UPT) BBPOM in Pontianak has the authority of intelligence and investigation in the field of Medicines and Food Control by the provisions of legislation. BPOM through BBPOM in Pontianak can take steps to prove Forensic Food and Medicines (Forensic Food and Medicine Science) which is a branch of forensic science related to the identification, analysis, and investigation of crimes related to food, beverages, medicines, and supplements when investigating criminal acts of illegal Medicines and Food trafficking. All discussions are based on the regulation (Omnibus Law) Law (Law) Number 17 of 2023 on health repealing Law (Law) Number 36 of 2009 on health.